BUSINESS ANALISYS OF SMOKE FRINGESCALE SARDINELLA (Sardinella fimbriata) AT LANJUT VILLAGE SINGKEP PESISIR SUB DISTRICT LINGGA REGENCY RIAU ISLANDS PROVINCE - Simatupang, Ismi Hidayat; Hendrik, Hendrik; Kusai, Kusai (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThis research about business analisys smoke fringerscale sardinella (Sardinellafimbriata) held on Mei 2018 at Lanjutvillage Singkep pesisir sub district Lingga regency Riau Islands province. This research aim to (1) find out total cost of smoke fringerscale sardinella (Sardinellafimbriata) business fund and (2) analize expediency business of smoke fringerscale sardinella (Sardinellafimbriata). Method used in this research was survey method which involve observation, interview, and documentation.Based on research result (1) input in smoke fringerscale sardinella business was aount of main ingredient on each businessmen with 25-35 m2 business space as much as 114-120kg/day and output in smoke fringerscale sardinella was production amount on each businessmen as much as 57-60kg /day, (2) average production cost on smoke fringerscale sardinella business with wide space 25-35 m2 as much as Rp 585.000, -/day up to Rp, 619.000-/day with total income as much as Rp 855.000, -/day up to Rp 900.000-/day and total profit as much as Rp270.000,-/day up to Rp 281.000,-/day and (3) smoke fringerscale sardinella business at Lanjut village was decent with RCR value>1, with FRR value>6,02 % and PPC value between 2,60 - 2,71 per period or ± 3 year. Keywords: SomkeFringescaleSardinella, Business Analisys, Lanjut Village